Peran Model RME Berbantuan Media LINCAH Terhadap Pemahaman Konsep Matematika Kelas III SDN 1 Pekalongan - Sholikatun Dewi Sri Hartiningsih; Marissa Jenyo Abda'u; Wulan Sutriyani; Eka Setya Budi (Universitas Islam Nahdlatul Ulama Jepara, 2022)
ABSTRAK Education is a way to improve and develop quality human resources in its entirety, through the educational process it is hoped that it will produce qualified future leaders of the nation. Education does not only play a role in knowledge, but also plays a role in shaping the character of the nation. In other words, education should form intelligent and characterized people, so that it will create a nation that excels in achievement and is polite to interact in accordance with the noble values of the nation. So that in the learning process in elementary schools, students gain knowledge in learning. Supporting effective learning requires tangible tools to achieve learning objectives. So it is necessary to apply appropriate learning models and learning media. This study aims to provide new innovations in the application of the RME model with the help of learning media, namely the LINCAH media (Lingkaran Fractions) in understanding the concept of class III material at SDN 1 Pekalongan which found 28 students. The research method used is a research approach in the form of library research. Data collection techniques in the form of observation and interviews. The results of the study are the low understanding of students in mathematical concepts, especially material. Mathematics, RME, Understanding the concept of Mathematics.